2016
DOI: 10.1080/21541248.2016.1215656
|View full text |Cite
|
Sign up to set email alerts
|

The mystery of oncogenicKRAS: Lessons from studying its wild-type counter part

Abstract: Using conditional knock-in mouse models, we and others have shown that despite the very high sequence identity between Nras and Kras proteins, oncogenic Kras displays a much stronger leukemogenic activity than oncogenic Nras in vivo. In this manuscript, we will summarize our recent work of characterizing wild-type Kras function in adult hematopoiesis and in oncogenic Kras-induced leukemogenesis. We attribute the strong leukemogenic activity of oncogenic Kras to 2 unique aspects of Kras signaling. First, Kras i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Despite the high degree of sequence identity between Kras and Nras proteins (.80%), we and others observed that oncogenic Kras is a much more potent oncogene than oncogenic Nras in myeloid diseases, demonstrated by earlier disease onset, more severe phenotypes, and shorter survival in Kras G12D/1 mice compared with Nras G12D/1 , Nras G12D/G12D , and Nras Q61R/1 mice (reviewed in Chang et al 48 ). Interestingly, when activated throughout the hematopoietic system, Kras G12D/1 mice never developed B-cell malignancies whereas a fraction of oncogenic Nras mice did.…”
Section: Kras Mutations Vs Nras Mutations In MMmentioning
confidence: 59%
“…Despite the high degree of sequence identity between Kras and Nras proteins (.80%), we and others observed that oncogenic Kras is a much more potent oncogene than oncogenic Nras in myeloid diseases, demonstrated by earlier disease onset, more severe phenotypes, and shorter survival in Kras G12D/1 mice compared with Nras G12D/1 , Nras G12D/G12D , and Nras Q61R/1 mice (reviewed in Chang et al 48 ). Interestingly, when activated throughout the hematopoietic system, Kras G12D/1 mice never developed B-cell malignancies whereas a fraction of oncogenic Nras mice did.…”
Section: Kras Mutations Vs Nras Mutations In MMmentioning
confidence: 59%
“…Although typically secondary events late in leukemogenesis, 51 mutations in the RAS pathway are found in AML in general and at a high frequency in MLLr leukemia (;10% NRAS and KRAS mutations), 52 and they play a role in disease pathogenesis. 53,54 In a negative-selection screen of epigenetic regulators in mouse MLL-AF9 leukemia cells overexpressing an activating form of Ras, NRas G12D , Shi et al 26 did not observe depletion of JmjC sgRNAs e20.1, e21.1, e22.1, e23.1, and e23.2. RAS mutations are also found in common AML cell lines, including NOMO1 (KRAS G13D ) and THP1 (NRAS G12D ; Broad Institute Cancer Cell Line Encyclopedia).…”
Section: Jmjd1c Regulates the Interleukin-3 Signaling Pathwaymentioning
confidence: 98%
“…Despite their similar expression patterns and high protein sequence similarities, we found that Kras G12D is a much more potent oncogene than oncogenic Nras; expression of Kras G12D , through either pI-pC induction or leaky expression of Mx1-Cre, drives an acute myeloproliferative neoplasm (MPN) and leads to much earlier lethality than oncogenic Nras in mice (reviewed in Chang et al 5 ). Consistently, juvenile myelomonocytic leukemia with heterozygous somatic KRAS mutations are particularly aggressive and generally require an urgent bone marrow transplantation therapy.…”
Section: Introductionmentioning
confidence: 99%